Vaccinia Virus Gene B7R Encodes an 18-kDa Protein That is Resident in the Endoplasmic Reticulum and Affects Virus Virulence - Price, N; Tscharke, D; Hollinshead, M; Smith, G (Elsevier, 2000)
This paper presents a characterisation of vaccinia virus (VV) gene B7R that was predicted to encode a polypeptide of 182 amino acids with an N-terminal signal peptide. In vitro transcription and translation analysis showed the B7R gene product was a 21-kDa protein that, in the presence of microsomes, was processed into an 18-kDa mature form. The 18-kDa form associated with the microsomal membranes and was within the lumen of the vesicle where it was inaccessible to exogenous protease or an antibody raised against the B7R C terminus. Within VV-infected cells, the 18-kDa form of B7R was detected late during infection in the endoplasmic reticulum where it colocalised with protein disulphide isomerase. The B7R protein was detected neither in the culture supernatant nor associated with virus particles. A virus deletion mutant lacking the B7R gene and a revertant virus were constructed. Compared to wild-type and revertant viruses, the deletion mutant replicated normally in cell culture and had unaltered virulence in a murine intranasal model of infection. However, the deletion mutant was attenuated in a murine intradermal model where it induced a smaller lesion than the control viruses.